Analisis Pengaruh Pertumbuhan Ekonomi, Indeks Pembangunan Manusia Dan Belanja Pemerintah Terhadap kemiskinan Di Kabupaten Blora - Muntina Juliana Evita; Wiwin Priana Primandhana (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
The purpose of this study is to determine and analyze the effect of economic growth, human development index and government spending in Blora district. The research data used is time series data in 2009-2020 from the Central Java Statistics Agency and Blora Regency. The research method used is quantitative research and uses multiple linear regression analysis techniques with the Ordinary Least Square (OLS) model with the help of the IBM SPSS (Statistics Program For Social Science) data processing computer program version 26.0. The results of this study explain that economic growth and the human development index have a positive and significant impact on poverty, while government spending has a negative and significant effect on poverty. Together these three variables have a significant influence on poverty in Blora Regency.